INDONESIAN COLLEGE STUDENTS’ PERCEPTIONS OF TOEFL PREPARATION CLASS - Siti Masfufah (EduLite: Journal of English Education, Literature and Culture, 2018)
This is the report of a pilot study of a dissertation. This study investigated what Indonesian students perceived of the TOEFL Preparation class.  The researcher interviewed 11 students of Economics. The students’ age ranged from 18 – 23 years old.  Seven of them had a job. Three of them were planning to have a job. The other one was a full-time student. This research revealed that the majority of the students were satisfied with the TOEFL Preparation class. The teacher helped them understand English compared to their knowledge before taking the TOEFL class. However, the students suggest that the duration for each meeting should be at least 120 minutes. Beside, the teacher should provide group work activities and homework. In addition, the teacher should come to class on time. Some recommendations of the findings are discussed in this paper.